A 12‐week integrative exercise program improves self‐reported mindfulness and interoceptive awareness in war veterans with posttraumatic stress symptoms. Issue 4 (27th October 2017) - Mehling, Wolf E.; Chesney, Margaret A.; Metzler, Thomas J.; Goldstein, Lizabeth A.; Maguen, Shira; Geronimo, Chris; Agcaoili, Gary; Barnes, Deborah E.; Hlavin, Jennifer A.; Neylan, Thomas C.
Abstract: Objective: Innovative approaches to the treatment of war‐related posttraumatic stress disorder (PTSD) are needed. We report on secondary psychological outcomes of a randomized controlled trial of integrative exercise (IE) using aerobic and resistance exercise with mindfulness‐based principles and yoga. We expected—in parallel to observed improvements in PTSD intensity and quality of life—improvements in mindfulness, interoceptive bodily awareness, and positive states of mind. Method: A total of 47 war veterans with PTSD were randomized to 12‐week IE versus waitlist. Changes in mindfulness, interoceptive awareness, and states of mind were assessed by self‐report standard measures. Results: Large effect sizes for the intervention were observed on Five‐Facet Mindfulness Questionnaire Non‐Reactivity (d = .85), Multidimensional Assessment of Interoceptive Awareness Body Listening (d = .80), and Self‐Regulation (d = 1.05). Conclusion: In a randomized controlled trial of a 12‐week IE program for war veterans with PTSD, we saw significant improvements in mindfulness, interoceptive bodily awareness, and positive states of mind compared to a waitlist.